Mexican American Fertility Patterns - Bean, Frank D. (University of Texas Press, 2021)
The Mexican American population is the fastest growing major racial/ethnic group in the United States. During the decade 1970-1980, the Mexican origin population increased from 4.5 million to 8.7 million persons. High fertility, not immigration, was responsible for nearly two-thirds of this growth. Recent and historical evidence shows that women of Mexican origin or descent bear significantly more children than other white women in the United States. Mexican American Fertility Patterns clarifies the nature and magnitude of these fertility differences by analyzing patterns of childbearing both across ethnic groups and within the Mexican American population. Using data from the 1970 and 1980 U.S. Censuses and from the 1976 Survey of Income and Education, the authors evaluate various hypotheses of cultural, social, demographic, and/or economic factors as determinants of fertility differences. Empirical analyses center on the interrelationships between fertility and generational status, language usage and proficiency, and female education. This timely report concludes that Mexican American fertility is closest to that of other whites under conditions of greater access to the opportunity structures of the society